The effect of six days of dietary nitrate supplementation on performance in trained CrossFit athletes. Issue 1 (December 2016) - Kramer, Samuel; Baur, Daniel; Spicer, Maria; Vukovich, Matthew; Ormsbee, Michael
Abstract Background While it is well established that dietary nitrate reduces the metabolic cost of exercise, recent evidence suggests this effect is maintained 24 h following the final nitrate dose when plasma nitrite levels have returned to baseline. In addition, acute dietary nitrate was recently reported to enhance peak power production. Our purpose was to examine whether chronic dietary nitrate supplementation enhanced peak power 24 h following the final dose and if this impacted performance in a heavily power-dependent sport. Methods In a double-blind, randomized, crossover design, maximal aerobic capacity, body composition, strength, maximal power (30 s Wingate), endurance (2 km rowing time trial), and CrossFit performance (Grace protocol) were assessed before and after six days of supplementation with nitrate (NO) (8 mmol·potassium nitrate·d−1 ) or a non-caloric placebo (PL). A 10-day washout period divided treatment conditions. Pairedt -tests were utilized to assess changes over time and to compare changes between treatments. Results Peak Wingate power increased significantly over time with NO (889.17 ± 179.69 W to 948.08 ± 186.80 W;p  = 0.01) but not PL (898.08 ± 183.24 W to 905.00 ± 157.23 W;p  = 0.75). However, CrossFit performance was unchanged, and there were no changes in any other performance parameters. Conclusion Consuming dietary nitrate in the potassium nitrate salt form improved peak power during a Wingate test, but did not improve elements of strength or endurance in male CrossFit athletes.